To understand the role of ICT and industry 4.0 in Hotel industry of Uzbekistan - Turaeva Ezoza Farrux qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The main aim of this research is to understand the role of innovative Information and Communication Technology Solution in Uzbekistan hotel and tourism sector and analyze its impact on industry 4.0 development within Uzbekistan Hotels (Hyatt Regency and Hilton hotels were taken as an example). A particular focus is paid to the ICT application benefits and challenges for hotel industry and in final parts some proper recommendations will be given to enhance their service quality, increase competitiveness and speed by usage of ICT and finally an individual reflection was provided to demonstrate how the module was useful and beneficial and how it affected to the author’s professional enhancement.